NILAI KEARIFAN LOKAL KAWASAN WISATA MENGGUNAKAN PENDEKATANGREEN MARKETING BERBASIS MASYARAKAT - Nawangsih Nawangsih (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
The research goal is to knowing about: value of local wisdom preserved in the tourist area as a tourist attraction, application of the approach of green marketing in an effort to preserve the value of local wisdom in the tourist area, attraction other potential supporters developed in the tourist area with green marketing approach and role of POKDARWIS to preserve the tourist areas.This study uses a qualitative method using a phenomenological approach. There is the approach with the special characteristic that happen in this location bamboo forets,using interviews, observation / observation and document research techniques.The research results are expected value of local wisdom is like traditions, customs owned by the community can be preserved. Green marketing approach serves as activity to keeping concept of local wisdom in the tourist area as environmentally sound educational of bamboo it can be exis and then can be iconic this location always good and useful to enviroinment and society arroun this place. Kelompok Sadar Wisata / POKARWIS give the contribute to bring a succesthe green marketing activity and the activity to be serve of the value local wisdom from the environmental concern